Combined familial C7 and C4B deficiency in an adult with meningococcal disease. - Chapel, H; Peto, T; Luzzi, G; Thompson, R; Fielder, A; Batchelor, JR (1987)
A case of meningococcal septicaemia is reported in an adult with a deficiency of the seventh component of complement combined with a deficiency of the B locus product of C4. A family study demonstrated that the two deficiencies were not linked. This is the first time that the individual alleles of C4 were determined in a patient with a deficiency of one component of the terminal pathway. It is possible that the heterogeneous clinical picture of a terminal pathway deficiency may, in part, be explained by the co-existence of other subtle complement defects.